1996
DOI: 10.1161/01.res.79.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Identification of m 1 Muscarinic Acetylcholine Receptors in Rat Ventricular Myocytes

Abstract: The expression of muscarinic acetylcholine receptor (mAChR) subtypes in freshly isolated adult rat ventricular myocytes was investigated by reverse transcription of cellular mRNA followed by amplification of cDNA using the polymerase chain reaction (PCR). After reverse-transcriptase PCR, bands were obtained corresponding to the expected sizes for the m1 and m2 but not for the m3 to m5 mAChRs. The identity of the m1 and m2 bands was confirmed by single-cell PCR, restriction digest mapping, and Southern blot ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 33 publications
2
48
0
Order By: Relevance
“…To determine effect of ASK1 expression on cardiac contractility, ASK1-expressing adult cardiac myocytes were field-stimulated at 1 Hz and Ca 2ϩ transients were measured as previously described. 34 Results show that ASK1 expression significantly inhibited both the rate and amplitude of Ca 2ϩ transients ( Figure 6E). These data strongly suggest that ASK1 activation induces cardiac contractile dysfunction.…”
Section: Ask1 Expression Induces Ctnt Phosphorylation and Contractilementioning
confidence: 83%
See 2 more Smart Citations
“…To determine effect of ASK1 expression on cardiac contractility, ASK1-expressing adult cardiac myocytes were field-stimulated at 1 Hz and Ca 2ϩ transients were measured as previously described. 34 Results show that ASK1 expression significantly inhibited both the rate and amplitude of Ca 2ϩ transients ( Figure 6E). These data strongly suggest that ASK1 activation induces cardiac contractile dysfunction.…”
Section: Ask1 Expression Induces Ctnt Phosphorylation and Contractilementioning
confidence: 83%
“…34 Briefly, cultured rat adult cardiomyocytes were rinsed in PBS and fixed for 15 minutes in 3% formaldehyde. The cells were then permeabilized for 15 minutes with 0.2% Triton X-100 followed by drying on a glass slide.…”
Section: Indirect Immunofluorescence Confocal Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were then measured according to the manufacturer's protocol (Amersham Biosciences). Intracellular Ca 2ϩ was measured as previously described (39). In brief, cells were grown on glass coverslips.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that, of the five mAchR subtypes identified to date, only the m1 and m2 subtypes are expressed in adult mammalian cardiac tissues (3,4). According to these reports, the m2 mAchR, which is expressed at a much higher level than the m1 mAchR, triggers the inhibitory response while m1 receptor activation elicits, when stimulated by higher concentrations of agonist, a compensatory excitatory effect on heart function.…”
mentioning
confidence: 99%